Analisis Kesesuaian Konsep dan Representasi Visual pada Mata Pelajaran Biologi Pokok Bahasan Sistem Imun pada Anime Cells at Work - Suci Rahmawati; Akhmad Akhmad; Suparno Putera Makkadafi; Masitah Masitah; Zenia Lutfi Kurniawati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the suitability of the concept of the immune system and the visual representation presented in the anime Cells at Work and the potential of the anime Cells at Work as an alternative learning medium. The data in this study are sentences that show the concept of the immune system and illustrations that show the visual representation contained in the anime Cells at Work. The data collection used is the observation method, the documentation method, and the literature study method. The data analysis technique used by the researcher is a qualitative descriptive technique. The results of the data analysis show that most of the concepts of the immune system are very much in line with current biological knowledge, season 1 of the anime shows a higher level of compatibility than season 2. Based on this, it is concluded that the Cells at Work anime can be used as an alternative learning medium, but it must still be accompanied by a teacher before and after the anime video is aired.